The ordinariness and extraordinariness of resistance: Young Bangladeshi professional women doing/undoing gender. (February 2023) - Sultana, Shaila; Deumert, Ana
Highlights: The paper problematises the way South Asian women are considered normatively in the colonial, post-colonial, and developmental discourses. Bangladeshi professional women playfully subvert the discourses that are traditionally associated with South Asian women in their translingual practices in digital spaces. Bangladeshi professional women use a variety of semiotic resources in the carnivalesque performance of resistance. Resistance to patriarchal gender norms is both ordinary and extraordinary. Abstract: This article is part of a larger study that considers how middle-class Bangladeshi women perform gender in online and offline contexts, the kinds of discourses they draw on, and the translingual resources that they engage with. In developing our argument, we first discuss colonial and post-colonial discourses about South Asian women. These historical discourses are still present in contemporary society and shape gender expectations as well as gender performativity. Four Bangladeshi professional women (aged 28–32) were part of the larger study, which combined digital ethnography with interviews. In this paper, we focus on one participant (called Katrina). We discuss, in detail, one Facebook interaction, where Katrina and her friends playfully subvert the discourses that are traditionally associated with South Asian women; gender expectations are challenged and a variety of semiotic resources are used in the carnivalesque performance of resistance. Following this, we consider the interview data which is less playful and translingual. In the interview resistance against gender norms is articulated differently, not as a playful collective engagement, punctuated with laughter, but as struggle and compromise. We argue that resistance to patriarchal gender norms is thus both ordinary and extraordinary: it is ordinary in the sense that it is everyday, and it is extraordinary in that it draws on highly creative forms of languaging and is embedded in struggles that reach back into history, while at the same time create unsettling anxieties and conflicted experiences in the here-and-now.